Guests’ perceived value, satisfaction and word of mouth in syariah compliant hotel / Azmira Zulkharnain - Zulkharnain, Azmira (2013)
A large growing numbers of Muslim, the increasing intra-regional travelling patterns among the Middle Eastern travellers with high spending power and the current tourism trends slightly influenced the hotel companies in this region to capture the Muslim market in the industry. This positive development together with the increasing demand and greater concerned of Muslim travellers on matters related to Islamic hospitality services have led to the interest of hotel companies to turn into Syariah Compliant hotel practices and the concept starts spreading into the Muslim countries globally. The success of Syariah hotel from Muslim guest view could be guided by observing Islamic teachings and practise in hospitality activities. This study is a trial to explore which Islamic dimension attributes of hotels could be used as base for tailoring Syariah compliant hotel package. Four guest hotel attributes are discussed to examine the Muslim guest perceived value of Syariah compliant hotel and its association with satisfaction and word of mouth. Two major dimensions are identified which include tangible: halal and cleanliness; availability of prayer facilities, and intangible: syariah dress code; separate facilities for men and women. It is argued that these factors creates attention to perception and as such, has an implication on word of mouth. Quantitative data collections serve as an approach through questionnaires towards Syariah hotel guest. This paper conceptually discusses the attributes of the tourist in Malaysia which have attract their perception of value and how it implicates satisfaction and word of mouth.